2018
DOI: 10.1002/dta.2446
|View full text |Cite
|
Sign up to set email alerts
|

In vitro phase I metabolism of three phenethylamines 25D‐NBOMe, 25E‐NBOMe and 25N‐NBOMe using microsomal and microbial models

Abstract: Numerous 2,5-dimethoxy-N-benzylphenethylamines (NBOMe), carrying a variety of lipophilic substituents at the 4-position, are potent agonists at 5-hydroxytryptamine (5HT ) receptors and show hallucinogenic effects. The present study investigated the metabolism of 25D-NBOMe, 25E-NBOMe, and 25N-NBOMe using the microsomal model of pooled human liver microsomes (pHLM) and the microbial model of the fungi Cunninghamella elegans (C. elegans). Identification of metabolites was performed using liquid chromatography-hig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
10
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 39 publications
0
10
0
Order By: Relevance
“…17 The group of Fu reported the first studies investigating the biotransformation of a chemical class of NPS using C. elegans (strain ATCC 10028b). 21 Our results showed that C. elegans was capable of generating one-third of the metabolites identified in pHLM. 18,19 We previously identified the metabolites of the three phenethylamines (25D-NBOMe, 25E-NBOMe, and 25 N-NBOMe) using pHLM and the fungi C. elegans.…”
mentioning
confidence: 58%
See 4 more Smart Citations
“…17 The group of Fu reported the first studies investigating the biotransformation of a chemical class of NPS using C. elegans (strain ATCC 10028b). 21 Our results showed that C. elegans was capable of generating one-third of the metabolites identified in pHLM. 18,19 We previously identified the metabolites of the three phenethylamines (25D-NBOMe, 25E-NBOMe, and 25 N-NBOMe) using pHLM and the fungi C. elegans.…”
mentioning
confidence: 58%
“…18,19 We previously identified the metabolites of the three phenethylamines (25D-NBOMe, 25E-NBOMe, and 25 N-NBOMe) using pHLM and the fungi C. elegans. 21 Our results showed that C. elegans was capable of generating one-third of the metabolites identified in pHLM.…”
mentioning
confidence: 58%
See 3 more Smart Citations